2013
DOI: 10.1016/j.diii.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Value of transrectal power Doppler sonography in the detection of low-risk prostate cancers

Abstract: A normal PDS in patients presenting a PSA level less than 10 ng/ml and a DRE without anomaly may be used to put off the indication for a biopsy in order to reduce their number as well as the risks of overtreatment for a latent cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Various authors reported additional value of the Doppler techniques over TRUS [9,16,18]. For Eisenberg et al [22], adding PDS to TRUS improved specificity from 47 to 74 %, although the sensitivity decreased from 58 to 47 %.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various authors reported additional value of the Doppler techniques over TRUS [9,16,18]. For Eisenberg et al [22], adding PDS to TRUS improved specificity from 47 to 74 %, although the sensitivity decreased from 58 to 47 %.…”
Section: Discussionmentioning
confidence: 99%
“…The power Doppler mode searched for the presence of intralesional vessels in a suspect lesion in the B-mode sonography. A visible lesion in B mode was hypervascularised if at least one vessel in this lesion was clearly identified [18] (Fig. 1).…”
Section: Ultrasound Semiology and Power Dopplermentioning
confidence: 99%
See 2 more Smart Citations
“…Studies suggest that on CDUS and PDUS, hypervascular and hypovascular lesions are associated with higher and lower Gleason scores, respectively (Fig. 1B) (17,18).…”
Section: Color and Power Doppler Ultrasoundmentioning
confidence: 99%